2010
DOI: 10.3171/2009.7.jns081504
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal transclival resection of chordomas: operative technique, clinical outcome, and review of the literature

Abstract: The endonasal endoscopic transclival approach represents a less invasive and more direct approach than a transcranial approach to treat certain moderate-sized midline skull base chordomas. Longer follow-up is necessary to determine comparability to transcranial approaches for long-term control. Large tumors with significant extension lateral to the carotid artery may not be suitable for this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 32 publications
4
137
0
8
Order By: Relevance
“…We were able to achieve > 95% resection rate in 81% of the cases for which a GTR was attempted. This rate agrees well with that of Fraser et al, 16 who reported an 87% success rate in achieving > 95% resection of clival chordomas with an endoscopic endonasal transclival technique. They cited tumor extension beyond the ICAs as the most important limitation to obtaining a GTR.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We were able to achieve > 95% resection rate in 81% of the cases for which a GTR was attempted. This rate agrees well with that of Fraser et al, 16 who reported an 87% success rate in achieving > 95% resection of clival chordomas with an endoscopic endonasal transclival technique. They cited tumor extension beyond the ICAs as the most important limitation to obtaining a GTR.…”
Section: Discussionsupporting
confidence: 82%
“…12,[14][15][16]20,[25][26][27][28][29][30] Our experience with clival lesions accessed using the EEEA complements the experience of others in that this approach can be highly effective in removing these surgically challenging lesions. We were able to achieve > 95% resection rate in 81% of the cases for which a GTR was attempted.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent endoscopic studies have shown favorable rates of gross total removal. For example, Fraser et al [ 44 ] achieved > 95% tumor resection in seven (87%) of eight patients in whom complete tumor resection was the goal. Stippler et al [ 117 ] and Dehdashti et al [ 27 ] reported GTR resection rates for clival chordomas of 67% and 58% with CSF leak rates of 25% and 33%, respectively.…”
Section: Clival Chordomasmentioning
confidence: 99%
“…Likewise, the tip of the instrument, where the aspiration occurs, is not easily visualized with a colinear, parallel endoscope, which provides better visualization for the side of the instrument. 4,5 Craniopharyngiomas, adenomas, and chordomas have a recurrence rate directly correlated with the percent of resection. 11 An ideal instrument for achieving this goal using endoscopic visualization would be a long, narrow side-cutting instrument whose tip and noncutting side could be placed in proximity to critical neurovascular structures for resection of firm tumors in a narrow working space without heating the surrounding tissue.…”
mentioning
confidence: 99%